DESIGN AND CONSTRUCTION OF E-LEARNING MEDIA MOBILE BASED USING ANDROID STUDIO - Aminuddin, Harun; Nirsal, Nirsal (Informatika, Universitas Jenderal Soedirman, 2024)
In the increasingly developing digital era, technological transformation has had a significant impact on various sectors, including education. This phenomenon gives rise to a new paradigm in the teaching and learning process, which is specifically known as educational technology or e-learning. This research aims to design an e-learning application. The main aim of this application is so that schools can keep up with technological developments that are developing rapidly in the world of education and also make it easier for teachers and students to provide information and increase learning hours that can be accessed by teachers and students anytime and anywhere. The type of research used is the Research and Development (R&D) method. The application development model used in this research involves four stages, namely observation, interviews and literature study. The application used in the creation system is Android Studio. The programming languages ​​used in designing this e-learning are HTML/CSS, PHP, Java Script and Kotlin. The result of this research is an application used by teachers and students at SDN 7 Ponjalae in the teaching and learning process using an electronic learning system to make it easier to access learning anywhere and anytime. This e-learning application has been tested using a black box by obtaining media expert validation test results of 3.90, including in the Very Good category.